PSYCHOLINGUISTIC ANALYSIS ON LANGUAGE DISORDER OF THE MAIN CHARACTER WITH ASPERGER SYNDROME IN “PLEASE STAND BY” MOVIE - Syahraini Husna Br Lubis; Iskandar Zulkarnain; Wiki Tedi Rahmawati (English Education Study Program FKIP Universitas Alwashliyah Medan, 2022)
This study dealt with the language disorder of the main character in